Sweet immunity in the plant circadian regulatory network - Bolouri Moghaddam, Mohammad Reza (Journal of experimental botany, 2013)
All organisms have an internal timing mechanism, termed the circadian clock, to anticipate the light/dark cycle. The clock, with an oscillating rhythm that approximates 24h, is a rather robust system persisting to a great extent in continuous light and dark. It is widely accepted that plant growth and development are regulated by the clock, hormones, and sugar signals. On the one hand, sugar signalling can affect circadian rhythms by altering the expression pattern of clock-regulated genes. More in particular, the clock seems to be particularly sensitive to sucrose-mediated signalling which is also associated with immunity and abiotic stress responses. Also, hormonal interaction with the clock can contribute to appropriate plant immune responses. Recent data show a prominent role for the clock in growth and stress responses. On the other hand, the clock seems to be essential in controlling the gene expression and activity of an array of carbohydrate-metabolizing enzymes, suggesting a complex reciprocal relationship between the clock and metabolic signalling processes. Therefore, the clock fulfils a crucial role at the heart of cellular networks. The players involved in the complex plant circadian network and their possible contribution to the novel 'sweet immunity' concept are discussed